Food control and biosecurity - Holban, Alina Maria; Grumezescu, Alexandru Mihai (Academic Press, 2018)
Food Control and Biosecurity, Volume Sixteen, the latest release in the Handbook of Food Bioengineering series, is an essential resource for anyone in the food industry who needs to understand safety and quality control to prevent or reduce the spread of foodborne diseases. The book covers information from exporter to transporter, importer and retailer, and offers valuable tools to measure food quality while also addressing government standards and regulations for food production, processing and consumption. The book presents cutting-edge methods for detecting hazardous compounds within foods, including carcinogenic chemicals. Other related topics addressing food insecurity and food defense are also discussed. - Resumé vydavatel
Keywords: bezpečnost potravin; management jakosti; kvalita potravin; biotechnologie; food safety; quality control; food quality; biotechnology; příručky; elektronické knihy; handbooks and manuals; electronic books